2017
DOI: 10.3892/ol.2017.7520
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA FAM83H‑AS1 is associated with the prognosis of colorectal carcinoma and promotes cell proliferation by targeting the Notch signaling pathway

Abstract: Abstract. The long non-coding RNA, FAM83H antisense RNA 1 (head to head) (FAM83H-AS1), has exhibited a functional role as an oncogene in a number of different types of cancer. The aim of the present study was to reveal the dysregulation of FAM83H-AS1 in colorectal carcinoma (CRC) samples and elucidate its underlying associations with the Notch signaling pathway. The expression profiles of FAM83H-AS1 and two Notch signaling-associated molecules, Notch1 and Hes family basic-helix-loop-helix transcription factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 34 publications
1
57
0
Order By: Relevance
“…FAM83H-AS1 was consistently over expressed in breast tumor samples and overall survival analysis of TCGA data sets showed poor prognosis of the up regulated group which are in agreement with other studies in breast, colorectal and lung cancer (Lu et al, 2018;Yang et al, 2016a;Yang et al, 2016c;Zhang et al, 2017). Functional studies have demonstrated that knock-down of FAM83H-AS1 proliferative potential through MET/EGFR signaling in lung adenocarcinoma and NOTCH1 signaling pathway in colorectal cancer.…”
Section: Discussionsupporting
confidence: 89%
“…FAM83H-AS1 was consistently over expressed in breast tumor samples and overall survival analysis of TCGA data sets showed poor prognosis of the up regulated group which are in agreement with other studies in breast, colorectal and lung cancer (Lu et al, 2018;Yang et al, 2016a;Yang et al, 2016c;Zhang et al, 2017). Functional studies have demonstrated that knock-down of FAM83H-AS1 proliferative potential through MET/EGFR signaling in lung adenocarcinoma and NOTCH1 signaling pathway in colorectal cancer.…”
Section: Discussionsupporting
confidence: 89%
“…LncRNA H19 has been reported to promote the apoptosis of hippocampal neurons by inhibiting let‐7b . LncRNA UCA1 inhibits seizures and brain damage caused by epilepsy by modulating the miR‐495/Nrf2‐ARE signaling pathway …”
Section: Discussionmentioning
confidence: 99%
“…24 LncRNA UCA1 inhibits seizures and brain damage caused by epilepsy by modulating the miR-495/Nrf2-ARE signaling pathway. 25 LncRNA GAS5 plays an important regulatory role in cancer progression, and it can inhibit oncogenes by inhibiting tumor cell proliferation, promoting apoptosis, and inhibiting cell migration and invasion. 26 Thus, we set out to establish a rat epilepsy model as well as a cell epilepsy model in order to detect the expression levels of IncRNA GAS5.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more studies focused on implicating the role of lncRNAs in diseases including cancers [25][26][27]. Some studies had reproted that lncRNA FAM83H-AS1 was associated with many types of cancers such as breast cancer [28], colorectal cancer [29] and colon cancer [30]. However, the function and mechanism of FAM83H-AS1 in OC has not been systemically studied.…”
Section: Discussionmentioning
confidence: 99%